Septic Pulmonary Embolism Case Report: Optimal Outcome after Insertion of an Inferior Vena Cava Filter in a Patient with Staphylococcus aureus Bacteraemia. (10th May 2010) - Esteves, Isabel; Castro, Sofia Vidal; Abecasis, Francisco; Camilo, Cristina; Vieira, Marisa; Gama, Dinis da; Correia, Manuela
Abstract : A 14-year-old patient presented with bilateral pneumonia and pleural effusions, septic arthritis of the hip, deep venous thrombosis, and pulmonary thromboembolism. Methicillin-sensitive Staphylococcus aureus ( S. aureus ) containing the Panton Valentine Leukocidin (PVL) genes was isolated. Contraindication to anticoagulation prompted inferior vena cava filter placement. He completed 4 weeks of treatment with flucloxacillin, with good clinical outcome. S. aureus containing PVL genes should be sought in cases of necrotizing pneumonia as it seems to increase the risk of severe multifocal infection and thrombotic complications. There are few reports of placement of filters during S. aureus sepsis and bacteraemia. This case highlights that when anticoagulation is not feasible, an inferior vena cava filter can be inserted safely, even in patients with active sepsis and high risk for seeding of the filter. Long-term follow-up confirmed a successful outcome with sterilization of the septic thrombosis with no further pulmonary embolism or additional sepsis episodes.